Survey to architects: challenges to inspection and diagnosis in historical residential buildings - Gonçalves, J. (2017)
Using a web query among architects (n=57), we could identify the main obstacles found in the application of inspection and diagnosis procedures in historical residential buildings.  The results revealed that these procedures are not yet uniformly applied in this built heritage and pointed out the need to develop simplified methodologies and less resource-consuming methodologies, to ensure their applicability.